A year in the life of FaceHunter - Rodic, Yvan (London : Thames & Hudson, 2013)
Chronicles a year-long face-hunting expedition to more than 30 of the author's favourite fashion cities. This title covers the world's most stylish cities ranging from the established fashion capitals of New York, Milan and Paris to exciting new style centres in Africa, Asia and South America and even unexpected gems such as Baku.
Dust jacket folds out into poster.
boek
Keywords: Rodic, Yvan